Analysis of fine-line screen and stencil-printed metal contacts for silicon wafer solar cells - Shanmugam, Vinodh; Wong, Johnson; Peters, Ian Marius; Cunnusamy, Jessen; Zahn, Michael; Zhou, Andrew; Yang, Rado; Chen, Xiao; Aberle, Armin G.; Mueller, Thomas (IEEE Journal of Photovoltaics, 2015)
Primary challenges to fine-line silver printing for solar cells are achieving high aspect ratios and uniform lines with a low level of striations. This paper compares two high-throughput printing technologies, namely, printing by screens versus stencils. A statistical method is introduced to evaluate the quality of the printed front grid based on the distributions of printed metal line profiles, line segment conductance, overall electroluminescence (EL) pattern, and solar cell light current-voltage (I-V) characteristics. The model distribution, combined with finite-element modeling to predict realistic cell-level voltage variations, adequately describes all four kinds of characteristics. It predicts well the diverging performance of screen- and stencil-printed solar cells as the line width becomes less than 50 μm. Experimentally, the highest batch average efficiency of 18.8% was achieved on 156 mm × 156 mm p-type monocrystalline silicon solar cells printed with stencils having 30-μm line openings, using only 78 mg of silver paste per cell.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Dual printing; fine-line metallization; high efficiency; metal contacts; screen printing; silicon wafer solar cells; stencil printing